From the Court to the Laboratory: The Scientific Evolution of Handball through Global Research and Performance Outcomes - Jose M. Saavedra; Sveinn Þorgeirsson; Dimitris Hatzimanouii; Yolanda Escalante (Montenegrin Journal of Sports Science and Medicine, 2026)
The objectives of this study were: (i) to analyze the evolution in the number of articles published on handball and the citations received; (ii) to determine whether there is a relationship between scientific production and the number of medals won in the Olympic Games and World Championships; (iii) to identify the research topics with the highest publication rates in handball; and finally, (iv) to identify the most cited articles, as well as the journals and countries that published the most on handball. Articles published between January 1, 1980, and December 31, 2024, were retrieved from the Web of Science Core Collection database. For each article, the following information was analyzed: authors; journal (year, volume, issue, pages, DOI); institution and country; funding agency; number of citations; and research topic. Absolute values and percentages were presented for articles and citations per year. Regression analyses calculated the coefficients of determination for the relationships between the number of articles and year, citations and year, and medals and publications by country. A total of 1,412 articles were analyzed. Significant relationships were found between year and number of articles (R²=0.6625, p